2020
DOI: 10.5897/jmpr2019.6819
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Thymus vulgaris L. on renal and liver toxicity in wistar rats exposed to aluminum

Abstract: The main sources of human exposure to aluminum are found in the extensive presence of the metal in the environment and its growing industrial applications. The present study was carried out to determine the effectiveness of the Thymus vulgaris L. extract in alleviating aluminum chloride (AlCl 3 ) toxicity on biochemical and antioxidant parameters. The experiment's rats were divided into five groups: a control group; an intoxicated group (300 mg AlCl 3 /kg bw); and three other groups which were given AlCl 3 (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
3
2
0
Order By: Relevance
“…These findings demonstrate the role of free radicals in the oxidative damage induced by Al toxicity. Our observations are consistent with earlier research that has shown that Al uptake stimulates oxidative stress and inhibits antioxidant enzyme activity in hepatic tissues (Mokrane et al, 2020;Othman et al, 2020;El-Demerdash et al, 2022). The inhibition of antioxidant enzyme activity may arise due to the reduced biosynthesis of these enzymes underpinning higher intracellular levels of Al and/or the overproduction of free radicals (Nampoothiri et al, 2015).…”
Section: Discussion Discussion Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings demonstrate the role of free radicals in the oxidative damage induced by Al toxicity. Our observations are consistent with earlier research that has shown that Al uptake stimulates oxidative stress and inhibits antioxidant enzyme activity in hepatic tissues (Mokrane et al, 2020;Othman et al, 2020;El-Demerdash et al, 2022). The inhibition of antioxidant enzyme activity may arise due to the reduced biosynthesis of these enzymes underpinning higher intracellular levels of Al and/or the overproduction of free radicals (Nampoothiri et al, 2015).…”
Section: Discussion Discussion Discussionsupporting
confidence: 92%
“…Thus, the high nitrite levels suggest elevated NO levels in the liver. Our findings show a high nitrite level in Al-exposed animals compared to that in the control group, confirming other research results (Mokrane et al, 2020;Othman et al, 2020). NO reacts readily with superoxide radicals to form peroxynitrite, capable of causing cellular damage by instigating lipid peroxidation and protein adduct formation that contribute to cell damage (Kumar et al, 2013).…”
Section: Discussion Discussion Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The observed increase in serum activities of AST and ALT, as seen in Figures 1(a) and 1(b) , can be attributed to the cytotoxic effect of Al on the kidney membrane permeability [ 37 ], which could lead to the leakage of these enzymes from the cytosol into bloodstream, along with disruptions or dysfunction in their activation [ 38 ]. Conversely, a slight decrease in total protein levels observed in AlCl 3 -induced rats may be due to an increase in intracellular Al concentration, which has been shown to reduce protein synthesis [ 39 ], aligning with the findings of Nawel et al [ 40 ]. However, the administration of caffeine, vanillin, and their combination resulted in decreased activities of ALT and AST, as well as an increase in plasma protein concentration ( Figure 1 ).…”
Section: Discussionsupporting
confidence: 80%
“…Such accumulation may be due to the very high affinity of Al for transferrin, and this may explain why Al can interfere with iron metabolism. The toxic effect of Al on the liver and kidneys tissue is related to lipid peroxidation, which can induce significant harmful changes in some biochemical characteristics and redox status (Nawel et al, 2020). Therefore, the accumulation of Al in the kidney promoted degeneration in renal tubular cells (Mohammed et al, 2017).…”
Section: Discussionmentioning
confidence: 99%